Association between menopausal hormone therapy and risk of neurodegenerative diseases: Implications for precision hormone therapy. Issue 1 (13th May 2021) - Kim, Yu Jin; Soto, Maira; Branigan, Gregory L; Rodgers, Kathleen; Brinton, Roberta Diaz
Abstract: Introduction: The impact of menopausal hormone therapy (HT) on age‐associated Alzheimer's and neurodegenerative diseases (NDDs) remains unresolved. To determine the effect of HT, formulation, type, and duration on risk of NDDs, a retrospective analysis was performed using a 10‐year Humana claims dataset. Methods: Study population included women aged 45 years or older with or without claim records of HT medications. Patients diagnosed with NDDs including Alzheimer's disease (AD), Parkinson's disease (PD), dementia, multiple sclerosis (MS), and amyotrophic lateral sclerosis (ALS) were identified. Relative risk (RR) ratios and 95% confidence intervals (CI) for combined NDDs, or AD, PD, dementia, MS, and ALS were determined. Cumulative hazard ratios were determined to investigate the association between HT and NDDs at different age groups. Results: In 379, 352 women with or without claim records of HT, use of HT was associated with significantly reduced risk for combined NDDs (RR 0.42, 95% CI 0.40–0.43, P < 0.001). Average follow‐up time was 5.1 [2.3] years. Formulations containing natural steroids 17β‐estradiol and/or progesterone were associated with greater reduction in NDD risk. Oral‐ HT users showed significantly reduced RRs (0.42, 0.41–0.44, P < 0.001) for combined NDDs compared to non‐HT users. The RRs for transdermal‐HT users were significantly decreased for all‐cause dementia (0.73, 0.60–0.88, P = 0.001) and MS (0.55, 0.36–0.84, P = 0.005). Greatest reduction in risk of NDD, AD, and dementia emerged in patients aged 65 years or older. Further, the protective effect of long‐term therapy (>1 year) on combined NDDs, AD, PD, and dementia was greater compared to short‐term therapy (≤1 year). Discussion: HT was associated with reduced risk of all NDDs including AD and dementia, with greater duration of therapy and natural steroid formulations associated with greater efficacy. These findings advance precision HT to prevent NDDs including AD.